Pulmonary miRNA expression after polytrauma depends on the surgical invasiveness and displays an anti-inflammatory pattern by the combined inhibition of C5 and CD14 - Zhou, Nan; Groven, Rald V. M.; Horst, Klemens; Mert, Ümit; Greven, Johannes; Mollnes, Tom Eirik; Huber-Lang, Markus; van Griensven, Martijn; Hildebrand, Frank; Balmayor, Elizabeth R. (Frontiers in Immunology, 2024)
Background Respiratory failure can be a severe complication after polytrauma. Extensive systemic inflammation due to surgical interventions, as well as exacerbated post-traumatic immune responses influence the occurrence and progression of respiratory failure. This study investigated the effect of different surgical treatment modalities as well as combined inhibition of the complement component C5 and the toll-like receptor molecule CD14 (C5/CD14 inhibition) on the pulmonary microRNA (miRNA) signature after polytrauma, using a translational porcine polytrauma model. Methods After induction of general anesthesia, animals were subjected to polytrauma, consisting of blunt chest trauma, bilateral femur fractures, hemorrhagic shock, and liver laceration. One sham group (n=6) and three treatment groups were defined; Early Total Care (ETC, n=8), Damage Control Orthopedics (DCO, n=8), and ETC + C5/CD14 inhibition (n=4). Animals were medically and operatively stabilized, and treated in an ICU setting for 72 h. Lung tissue was sampled, miRNAs were isolated, transcribed, and pooled for qPCR array analyses, followed by validation in the individual animal population. Lastly, mRNA target prediction was performed followed by functional enrichment analyses.The miRNA arrays identified six significantly deregulated miRNAs in lung tissue. In the DCO group, were significantly upregulated compared to the ETC group. The miRNA expression profiles in the ETC + C5/CD14 inhibition group approximated those of the DCO group. Bioinformatic analysis revealed mRNA targets and signaling pathways related to alveolar edema, pulmonary fibrosis, inflammation response, and leukocytes recruitment. Collectively, the DCO group, as well as the ETC + C5/CD14 inhibition group, revealed more anti-inflammatory and regenerative miRNA expression profiles. Conclusions This study showed that reduced surgical invasiveness and combining ETC with C5/CD14 inhibition can contribute to the reduction of pulmonary complications.